Masters of the late 20th Century. - Icat, Beerzel (Beerzel : ICAT, 1993)
Baimatov, Gairat ; Stjirov, Michael ; Zaitsev, Slava ; Djalal, Bachodir ; Volnova, Irina ; Tzoezikov, Igor ; Waldman, Alexander ; Nasritdinov, Alisher ; Juldashev, Bachodir ; Esdouletov, Askar
Masters of the late 20th Century, ICAT Beerzel, 1993
boek